URGENSI PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK DI ERA GLOBALISASI (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2023)
Tulisan ini akan mengulas fenomena globalisasi yang memiliki dampak pada Pendidikan Agama Islam dan pembinaan akhlak, sebagian besar dampak tersebut membawa pengaruh negative bagi masyarakat terutama pelajar. Pendidikan Agama Islam adalah sebuah pembelajaran yang lebih membahas tentang agama termasuk tentang akhlak. Akhlak adalah perilaku yang baik. Akhlak berasal dari kata bahasa arab khuluk yang berarti tingkah laku, perangkai, atau tabiat. Pada awalnya Pendidikan Agama Islam dan pembinaan akhlak mengalami perkembangan setiap tahunnya, namun seiring perkembangan zaman yang semakin canggih dan teknologi yang semakin berkembang pesat hal tersebut mengalami penurunan diakibatkan masyarakat khususnya pelajar tidak mampu memanfaatkan perkembangan tersebut dengan baik, sehingga banyak menimbulkan pengaruh negative yang dapat merusak pendidikan dan akhlak. This paper will review the phenomenon of globalization which has an impact on Islamic education and the cultivation of morals, most of these impacts have a negative impact on society, especially students. Islamic education is a study that is more about religion, including about morals. Moral is the behavior of a person that is driven by a conscious desire without any coercion from anyone to do something good. Akhlak comes from the Arabic word khuluk which means behavior, coupling, or character. At first Islamic education and the cultivation of morals have developed every year, but over time The more sophisticated and the technology that is growing rapidly, it has decreased due to the community, especially students, not being able to take advantage of these developments properly, so that many negative effects that can damage education and morals.